Pre-service teachers evaluations of their cooperating teachers’ contribution to their professional training: questionnaire development - Zach, Sima; Sindiani, Mahmood (Frontiers in Education, 2025)
IntroductionThis study aimed at creating and validating a questionnaire for pre-service physical education teachers, as a means for evaluating the performance and contribution of their cooperating teachers to these students’ practical teacher training process.MethodThe questionnaire, consisting of 25 items – 24 Likert-scale questions and a yes/no question regarding participants’ willingness to select the same cooperating teacher for their practical training – was administered to a sample of 406 pre-service teachers. This sample included second- and third-year students, outstanding students, and individuals undergoing academic retraining.ResultsThe questionnaire was validated through content validity and exploratory factor analysis, resulting in three main factors: modeling teacher behavior, training and supervision in their field, and support and feedback.DiscussionGiven that schools and cooperating teachers play a crucial role in teacher training, this study offers valuable insights for enhancing teacher education programs and reducing novice teacher attrition by clarifying the role of cooperating teachers and establishing foundational elements for their professional development.